Negative Comparative Law: The Sanitization Enterprise - Legrand, Pierre (Revista de Investigações Constitucionais, 2023)
This article challenges four basic and intertwining assumptions informing orthodox comparative law: that a comparatist can exactly represent foreign law; that he can write about foreign law objectively; that he can state the truth regarding foreign law; and that he enjoys the subjective agency to overcome the obstacles on the way to the achievement of these goals. Comparatists-at-law being oblivious to their structural cognitive weakness, which makes the pursuit of these realizations irredeemably preposterous, a strong contrarian programme is necessary so as to bring comparative law to its epistemological senses and, in the process, to heighten the scholarly integrity and reliability of comparative interventions. This article succinctly formulates such an oppositional stance.